Social Commerce and its Behavior in MSMEs in Mexico During COVID-19 - López Ruiz, Elver Mariel; Salvador García, Yazmín Denisse (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To analyze the behavior of Social Commerce through the most used networks by MSMEs due to the COVID 19 pandemic, and to identify the products with the highest online sales in the digital market.MATERIAL AND METHOD: This work is prepared under a documentary analysis and a contextual qualitative methodology, with information from secondary sources such as: online newspapers, scientific articles, investment analysis, web pages and national studies. The 2020 financial year was considered, because it was a year in which many MSMEs closed operations due to the uncertainty and instability experienced by COVID-19 and social commerce was an alternative for sales as a digital channel through social networks more used by them.RESULTS: The most purchased identified items through social commerce were: clothing, accessories, electronics, and jewelry mostly; 51% of women and 49% of men with a medium-low socioeconomic level.CONCLUSIONS: Social networks have become the new and most used digital sales channel by MSMEs and active users.
Keywords: Social Commerce; Mexico; MSMEs; Pandemic; Social networks.